Basic sciences in normal and abnormal palate development - Jonathan R. Sandy; Nathan L. Brown (Universidade Estadual de Campinas, 2015)
Orofacial clefting is one of the most common congenital malformations with an incidence of 1 in 500 to 1000 live births. Cleft lip and cleft palate may occur in isolation, in combination or as part of one of the 400 or more syndromes linked to orofacial clefting. Clefting causes problems with feeding, speech, hearing and the dentition. Patients and their families bear a significant emotional burden. Despite the high frequency and significance of the malformation, the aetiology of nonsyndromic cleft lip and palate is poorly understood. It has a complex multifactorial aetiology, both population-based and laboratory-based research has identified numerous genetic and environmental factors as causative agents and the list is continually expanding. Leading scientists are now beginning to question whether this trait is too complex to fully understand. This report provides a comprehensive and up-todate review of research into palatogenesis and non-syndromic oral clefting